Conservation - Minded Behavior of the Field Practice Participants on Automotive Engineering Education Program - Sudarman, Sudarman; Suwahyo, Suwahyo; Burhan, M.; K, A. Mustamil (Universitas Negeri Semarang, 2018)
Conservation – Minded Behavior of Field Practice Participant On Automotive Engineering Education Program. This study was aimed at figuring out: 1) conservation – minded behavior, 2) knowledge conservation, 3) achievement motivation, and 4) the support of conservation knowledge and achievement motivation simultaneously or independently to the conservation – minded behaviour of the field practice participants on automotive engineering education program, Engineering Faculty. This study was conducted in Mechanical Engineering Department, Engineering Faculty, UNNES and industry in Semarang in the year of 2017. 33 students were involved as the samples of this study. The conservation – minded behavior data were gathered using observation sheet, conservation knowledge data by test and achievement motivation data were gathered using questionnaire. The data were then analysed using descriptive statistics, multi regression and communality. The descriptive analysis showed that: conservation-minded behaviour of the field practice participants was mostly high, the conservation knowledge was mostly low and achievement motivation was mostly high. The multi regression analysis showed that the knowledge conservation and achievement motivation contributed 35.4% to the conservation – minded behavior. The communality analysis showed that conservation knowledge of the field practice participants contributed 15% to the conservation – minded behavior, and achievement motivation distributed 17.8% to the conservation – minded behaviour. The suggestion from this study was that the automotive engineering education should make an effort to improve the conservation – minded knowledge.